Prostaglandin-like Activity in Ocular Inflammation - Eakins, K. E. (1972)
Aqueous humour samples from untreated patients with acute anterior uveitis were found to contain substantial amounts of prostaglandin-like activity. Little activity was found in aqueous from patients treated with steroids, and none (<2 ng/ml) was detected in aqueous from the uninflamed eyes of patients with cataract. Alkaline hydrolysis of the samples from inflamed eyes suggested the presence of both E and F prostaglandin-like activity. These results show that prostaglandins may be involved in acute anterior uveitis.